Remote sensing derived spatial patterns of glacier mass balance in Tibet - Spiess, Marinka (2016)
The climate has changed on the Tibetan Plateau. The air temperature has shown distinct increase since the 1960s, exceeding the increase in other land areas of the same latitudinal position in the Northern Hemisphere. The retreat of Tibetan glaciers in connection with climate change is of interest since the glacierized areas constitute important freshwater resources – which, among others, provide the basis for all livelihoods on the plateau. Furthermore, the glaciation and snow cover of Tibet are crucial to feedback mechanism in the global climate system. Glacier retreat has been documented in many areas of the Tibetan Plateau. Regional differences in glacier change across the Tibetan Plateau are evident. Measured glaciological, meteorological and hydrological data are largely absent due to difficult excess of the remote areas. Only few and spatially dispersed mass balance studies have been conducted to date. Remote sensing presents thus preferable methods in order to monitor Tibetan glacier change. In this thesis the Moderate-resolution Imaging Spectroradiometer (MODIS) snow product and MODIS Level 1 radiance Swath Data is used to derive snow line altitudes. The snow line altitude at the end of the ablation period provides a proxy for the equilibrium-line altitude (ELA) of a glacier. The variability of the annual ELA itself is a valuable proxy for the variability of glacier mass balance. The mass balances of different glaciers in a specific region often show very high correlations in their temporal variance even though the transient snowline elevation can vary across individual glaciers. In this thesis the former three facts are utilized to derive daily regional snow line altitudes and interannual ELAs on different glacierized regions distributed across the Tibetan Plateau. The regions of interest are the Western Nyainqêntanglha range, three areas in the mountains of the Transhimalayas, the Gurla Mandhata massif in the western Himalayas, the Muztagh Ata in the Pamirs, the Ulugh Muztagh ice cap in the Kunlun Shan ...